Tyramine Actions on Drosophila Flight Behavior Are Affected by a Glial Dehydrogenase/Reductase - Ryglewski, Stefanie; Duch, Carsten; Altenhein, Benjamin (Frontiers in Systems Neuroscience, 2017)
The biogenic amines OA and TA modulate insect motor behavior in an antagonistic manner. OA generally enhances locomotor behaviors such as Drosophila larval crawling and flight, whereas TA decreases locomotor activity. However, the mechanisms and cellular targets of TA modulation of locomotor activity are incompletely understood. This study combines immunocytochemistry, genetics, and flight behavioral assays in the Drosophila model system to test the role of a candidate enzyme for TA catabolism, named nazgul (Naz), in flight motor behavioral control. We hypothesize that the dehydrogenase/reductases Naz represents a critical step in TA catabolism. Immunocytochemistry reveals that Naz is localized in a subset of Repo positive glial cells with cell bodies along the motor neuropil borders and numerous positive Naz arborizations extending into the synaptic flight motor neuropil. RNAi knock-down of Naz in Repo positive glial cells reduces Naz protein level below detection level by Western blotting. The resulting consequence is a reduction in flight durations, thus mimicking known motor behavioral phenotypes as resulting from increased TA levels. In accord with the interpretation that reduced TA degradation by Naz results in increased TA levels in the flight motor neuropil, the motor behavioral phenotype can be rescued by blocking TA receptors. Our findings indicate that TA modulates flight motor behavior by acting on central circuitry and that TA is normally taken up from the central motor neuropil by Repo-positive glial cells, desaminated, and further degraded by Naz.